Web-Based Application to Measure Motoric Development of Early Childhood - Daviq Chairilsyah (Jurnal Pendidikan Usia Dini, 2019)
ABSTRACTParents and early childhood educators still find it difficult to find ways to self-identify children's motor development, there needs to be innovation that measures motoric development can be easily used by parents The purpose of this study is to identify indicators of motor development in early childhood, make measuring instruments, and create a web-based measurement application. This Research and Development methodology uses mix method data analysis. This research is located in Indonesia with a sample of 590 participants. The results of the study show that valid and reliable measurement instruments for motoric development from the results of testing as many as 97 indicators are considered high value. Applications made by Information Technology experts to produce a systematic performance measurement system, making it easier for users, teachers / parents who are famous to get the results of the examination quickly and accurately. The implications of research are expected to be able to build a measuring device with the application of technology that is more developed in aspects of child development in addition to motor development, to become a facility for assessing early childhood development that makes it easier for educators to use it.Keywords: Early Childhood, Motoric Development, Web Based Application Instrument.REFERENCESAli, A. (2012). Persepsi guru terhadap penggunaan kurikulum berasaskan bermain bagi aspek perkembangan bahasa dan literasi murid prasekolah. Malay Language Education Journal (MyLEJ), 2(1).  Azwar, S. (2014). Reliabilitas dan Validitas Edisi 4. yogyakarta: Pustaka Pelajar.Barnett, L. M., Stodden, D., Miller, A. D., Cohen, K. E., Smith, J. J., Dudley, D., … Morgan, P. J. (2016). Fundamental Movement Skills : An Important Focus Only Leads to a Limited Number, 219–225.Cairney, J., Clark, H. J., James, M. E., Mitchell, D., Dudley, D. A., & Kriellaars, D. (2018). The Preschool Physical Literacy Assessment Tool : Testing a New Physical Literacy Tool for the Early Years, 6(June), 1–9. https://doi.org/10.3389/fped.2018.00138Carson, H. J., Collins, D., & Carson, H. J. (2016). The fourth dimension : A motoric perspective on the anxiety – performance relationship The fourth dimension : A motoric perspective on the anxiety – performance relationship, 9858(February), 0–21. https://doi.org/10.1080/1750984X.2015.1072231Griffiths, A., Toovey, R., Morgan, P. E., Spittle, A. J., & Pe, M. (2018). Psychometric properties of gross motor assessment tools for children : a systematic review, 1–14. https://doi.org/10.1136/bmjopen-2018-021734Hasnida. (2014). Analisis Kebutuhan Anak Usia Dini. Jakarta: Luxima.Helmawati. (2015). Mengenal dan Memahami PAUD. Bandung: PT Remaja Rosdakarya.Hiryanto. (2013). Pemetaan Tingkat Pencapaian Mutu Program Pendidikan Anak Usia Dini (Paud) Di Propinsi DIY. Yogyakarta. Hurlock, E. B. (1999). Perkembangan Anak Jilid I. (Erlangga, Ed.). jakarta.Loprinzi, P. D., Davis, R. E., & Fu, Y. (2015). Early motor skill competence as a mediator of child and adult physical activity Early / Middle Childhood. PMEDR, 2, 833–838. https://doi.org/10.1016/j.pmedr.2015.09.015Malina, R. M. (2003). Motor Development during Infancy and Early Childhood : Overview and Suggested Directions for Research. International Journal of Sport and Health Science, 2(5), 50–66. Retrieved from http://www.soc.nii.ac.jp/jspe3/index.htmMonnas, L. B. (2018). Insight stories : Looking into teacher support in enhancing scientific thinking skills among pre-school students. Journal of Educational Sciences., 2(1), 19–25. Pendidikan, M., Kebudayaan, D. A. N., & Indonesia, R. Peraturan Menteri Pendidikan Dan Kebudayaan Republik Indonesia Nomor 137 Tahun 2014 Tentang Standar Nasional Pendidikan Anak Usia Dini (2014).Purna, R. ., & Kinasih, A. S. (2015). Psikologi Pendidikan Anak Usia Dini. Jakarta: PT. Indeks.Rao, N., Sun, J., Richards, B., Weber, A. M., Sincovich, A., Darmstadt, G. L., & Ip, P. (2018). Assessing Diversity in Early Childhood Development in the East Asia-Pacific.Richard, D. (2013). Aplikasi Teori Pembelajaran Motorik di Sekolah. yogyakarta: Diva Press.Rolina, N., & Muhyidin. (2015). Metode & Media Pembelajaran (jilid 4). In Ensiklopedia Pendidikan Anak Usia Dini. yogyakarta: Pustaka Insan Madani.Sani, N. A., & Yunus, F. (2018). Amalan Perancangan , Pelaksanaan dan Pentaksiran dalam Proses Pengajaran dan Pembelajaran Pranumerasi di Tadika Swasta. Jurnal Pendidikan Malaysia, 43(2), 101–110. https://doi.org/http://dx.doi.org/10.17576/JPEN-2018-43.02-10 AmalanSantioso, L. . (2016). Tes Minat dan Bakat Anak. Jakarta: Penebar Swadaya Group.Suyadi. (2014). Manajemen PAUD (TPA-KB-TK/RA). yogyakarta: Pustaka Pelajar.